BRICS as a Catalyst for Global Governance Transformation: Beyond Western Perceptions - Dylan Yanano Mangani (Vestnik MGIMO-Universiteta, 2024)
Scholarship on global political economy and global peace and security governance often depicts BRICS members as emerging powers with relatively limited experience in international leadership. These depictions underscore their contested regional leadership and ambiguous institutional, political, ideological, and socio-economic capacities to influence and reshape the global governance system. However, this article challenges some of these characterizations of BRICS members as inaccurate and rooted in Western exceptionalism. Employing a qualitative secondary research approach, it aims to analyze the role of BRICS as a new model for global governance by examining key institutional and political initiatives undertaken by the bloc, as well as by each of its member states.The analysis reveals that institutional initiatives such as the New Development Bank (NDB) demonstrate the BRICS’ capacity to deploy a combination of hard and soft power tools, thereby contributing to the emergence of multipolarity in the global governance architecture. These initiatives have exposed the world's developing regions to new experiences, resources, and understandings of the priorities of emerging powers. Furthermore, political responses to crises, such as turmoil in Zimbabwe, Libya, and Mali, as well as nuclear issues in Iran, where BRICS members have assumed mediatory, supportive, or leading roles, have sparked renewed interest in understanding BRICS as an alternative to traditional conceptions of global peace and security governance. Significantly, BRICS’ soft power diplomacy plays a pivotal role in projecting the bloc as an advocate of alternative global governance architecture and in dispelling negative perceptions. This objective is achieved through the BRICS’ transformative agenda, which offers alternative pathways for attaining international public goods in developing regions with shared historical and ideological affinities.